EFEKTIVITAS WEBSITE PEMEMERINTAH KABUPATEN KARANGANYAR SEBAGAI SUMBER INFORMASI KEPARIWISATAAN REMAJA - Dian Esti Nurati, Alfaridho Firdaus Widyahusada, Bedjo Sukarno & (Transformasi, 2016)
www.karanganyarkab.go.id is an official website launched by the government of Karanganyarregency, Central Java. Based on the comprehensiveness of the features and informationprovided, www.karanganyarkab.go.id is a great media fulfilling requirements to be a referenceand public information provider in obtaining information regarding Karanganyar regency,especially in Tourism in Karanganyar.The aim of this research is to find out the level ofeffectiveness with the official Karanganyar government website as a tourism information sourceamong teenagers in Karanganyar sub-district.The level of effectiveness with the official websiteas a tourism information provider among teenagers is almost fulfilling the requirements, butpromotion is still needed in developing the existence of the website in order to facilitate theinformation seekers in obtaining tourism information of Karanganyar regency.Keyword: Official Website of Karanganyar regency, Tourism Information, Teenagers